Respuesta :
Answer:
a. [tex]\mathbf{Y(s) = L \{y(t)\} = \dfrac{7}{s(s+1)}+ \dfrac{e^{-3s}}{s+1}}[/tex]
b. [tex]\mathbf{y(t) = \{7e^t + e^3 u (t-3)-7\}e^{-t}}[/tex]
Step-by-step explanation:
The initial value problem is given as:
[tex]y' +y = 7+\delta (t-3) \\ \\ y(0)=0[/tex]
Applying laplace transformation on the expression [tex]y' +y = 7+\delta (t-3)[/tex]
to get [tex]L[{y+y'} ]= L[{7 + \delta (t-3)}][/tex]
[tex]l\{y' \} + L \{y\} = L \{7\} + L \{ \delta (t-3\} \\ \\ sY(s) -y(0) +Y(s) = \dfrac{7}{s}+ e ^{-3s} \\ \\ (s+1) Y(s) -0 = \dfrac{7}{s}+ e^{-3s} \\ \\ \mathbf{Y(s) = L \{y(t)\} = \dfrac{7}{s(s+1)}+ \dfrac{e^{-3s}}{s+1}}[/tex]
Taking inverse of Laplace transformation
[tex]y(t) = 7 L^{-1} [ \dfrac{1}{(s+1)}] + L^{-1} [\dfrac{e^{-3s}}{s+1}] \\ \\ y(t) = 7L^{-1} [\dfrac{(s+1)-s}{s(s+1)}] +L^{-1} [\dfrac{e^{-3s}}{s+1}] \\ \\ y(t) = 7L^{-1} [\dfrac{1}{s}-\dfrac{1}{s+1}] + L^{-1}[\dfrac{e^{-3s}}{s+1}] \\ \\ y(t) = 7 [1-e^{-t} ] + L^{-1} [\dfrac{e^{-3s}}{s+1}][/tex]
[tex]L^{-1}[\dfrac{e^{-3s}}{s+1}][/tex]
[tex]L^{-1}[\dfrac{1}{s+1}] = e^{-t} = f(t) \ then \ by \ second \ shifting \ theorem;[/tex]
[tex]L^{-1}[\dfrac{e^{-3s}}{s+1}] = \left \{ {{f(t-3) \ \ \ t>3} \atop {0 \ \ \ \ \ \ \ \ \ t <3}} \ \ \ \right.[/tex]
[tex]L^{-1}[\dfrac{e^{-3s}}{s+1}] = \left \{ {{e^{(-t-3)} \ \ \ t>3} \atop {0 \ \ \ \ \ \ \ \ \ t <3}} \ \ \ \right.[/tex]
[tex]= e^{-t-3} \left \{ {{1 \ \ \ \ \ t>3} \atop {0 \ \ \ \ \ t<3}} \right.[/tex]
= [tex]e^{-(t-3)} u (t-3)[/tex]
Recall that:
[tex]y(t) = 7 [1-e^{-t} ] + L^{-1} [\dfrac{e^{-3s}}{s+1}][/tex]
Then
[tex]y(t) = 7 -7e^{-t} +e^{-(t-3)} u (t-3)[/tex]
[tex]y(t) = 7 -7e^{-t} +e^{-t} e^{-3} u (t-3)[/tex]
[tex]\mathbf{y(t) = \{7e^t + e^3 u (t-3)-7\}e^{-t}}[/tex]